Toward Our Reformation: From Legalism to Value-oriented Islamic Law and Jurisprudence By Mohammad Omar Farooq (London and Herndon, VA: IIIT, 2011. 323 pages.) (American Journal of Islam and Society, 2013)
Understandably, Muslims tend to bristle at the common quip by non-Muslims(especially in the West) that Islam is badly in need of a “Reformation” – referringto the sixteenth-century Protestant Reformation that, despite the violenceit unleashed in Europe for the next two centuries, did actually engendersome positive changes within the Catholic church. No people, regardless ofwho they are or where they live, like outsiders telling them that they need toset their house in order.This book, by contrast, is written by an insider telling other insiders (Muslims)that Islamic law needs serious revamping, a weighty charge indeed. Theauthor faces an extra hurdle based on the fact that he does not belong to thetraditional ulama class, the gatekeepers of Islamic jurisprudence. Farooq earneda Ph.D. in economics at the University of Tennessee, taught in the United Statesfor over a decade, and now heads the Bahrain Institute for Banking and Finance’sCentre for Islamic Finance. Rashid Rida would have said in his daythat Farooq represents the new face of the ulama: one well versed in many aspectsof the Islamic sciences and yet, because of his parallel expertise in themodern sciences, one who could provide indispensable guidance to society inthe name of Islam.Why does Islam need a reformation? Much of the book seeks to exposethe abuse, misapplication, and distortion of the Shari‘ah committed by statesand individual ulama alike, for it “is being used to rubber stamp extremist, violentbehavior, the abuse of women, and the unfair control and imprisonmentof human beings” (p. 16). Speaking of South Asia in particular, he writes thatthe following are “prevalent”: “[t]he torture and persecution of brides overtheir dowry, the throwing of acid onto girls who do not either want to accepta proposal of marriage or to concede to extramarital sex, the practice of honorkillings and so on …” (p. 86) ...